Sinergi Mahasiswa KKN: Digitalisasi UMKM, program Sosial, dan Religius Desa Tanjung Agas - Putra, Alvient Primadana; Fatullah, Ahmad Ari; ., Febiana; Alfajri, Muhammad Salman; Oktaviani, ⁠Nabilla; Sartika, Indri; Suci, Rahmad; Bakar, A Idham Abu; Firmansyah, M Zaky; Nashihin, Muhammad Fauzi Anwar; Pratama, Munif; Armando, Deri; Satma, Amanda Yaliza; Wulandari, Sinta; Sarah, Nadhea Mulia; Chandra, Rio Dwi; Yanti, Isnain Fitri Auli (Universitas Negeri Gorontalo, 2025)
The main goal of the 83rd Community Service Program (KKN) of Group 51 from Raden Fatah State Islamic University of Palembang in Tanjung Agas Village was to improve digital literacy and legal awareness, promote healthy lifestyles, strengthen religious values, and build community identity and social solidarity. To achieve these goals, the program included assisting MSMEs with digitalization through the use of QRIS, providing stunting prevention education for elementary school students, strengthening religious values through religious studies and Quran teaching, constructing a village identity monument as a symbol of pride, and offering legal consultation services through a Legal Aid Post (POSBAKUM). All activities were carried out using a participatory approach through discussions, technical assistance, and direct outreach, which allowed the community to be actively engaged in each stage of the program. In this way, the KKN program not only addressed the community’s practical needs but also encouraged independence and sustainable empowerment.